Surface Assimilation Of Phytoestrogens By Microbial Biopolymers - Sehgal, Shweta (My University, 2013)
In the present study the potential of microbial biopolymers to adsorb and remove phytoestrogens from the surface waters was examined. Extracellular Biopolymer producing bacteria were isolated and screened from various environmental sites, seventy one biopolymer producing bacteria were isolated of which 23 isolates showed highest flocculating activities and these were selected for their tendency to bind finally with phytoestrogens. Two isolates showing highest phytoestrogen removal activity were selected and further optimization studies were carried out. Different parameters for the effective adsorption of phytoestrogens were optimized i.e. effective dose of biopolymers and effect of time of contact on biopolymer and phytoestrogen binding. The observations from the study revealed that for coumestrol, a concentration of 1.5 mgml-1 of biopolymer FM17 and DS1 was found to be optimum and for Formononetin, Genistein and Biochanin A the optimum concentration was 1 mgml-1 and 1.5 mgml-1 respectively. The biopolymer FM17 showed maximum reduction (87%) of Genistein whereas biopolymer DS1 showed maximum reduction (72%) of Formononetin which was further confirmed by Langmuir isotherm. Compositional analysis of the biopolymers revealed them to be of anionic nature and principally composed of sugars and proteins.
MS, DBTES
Keywords: Biopolymers (extracellular), Flocculating activity, Phytoestrogen